Emerging technologies for genetic control systems in cellular therapies. (December 2022) - de Rossi, Jacopo; Arefeayne, Yafet; Robinson, Ashley; Segatori, Laura
Abstract : Progress in synthetic biology has enabled the construction of designer cells that sense biological inputs, and, in response, activate user-defined biomolecular programs. Such engineered cells provide unique opportunities for treating a wide variety of diseases. Current strategies mostly rely on cell-surface receptor systems engineered to convert binding interactions into activation of a transcriptional program. Genetic control systems are emerging as an appealing alternative to receptor-based sensors as they overcome the need for receptor engineering and result in cellular behaviors that operate over therapeutically relevant timescales. Genetic control systems include synthetic gene networks, RNA-based sensors, and post-translational tools. These technologies present fundamental challenges, including the requirement for precise integration with innate pathways, the need for parts orthogonal to existing circuitries, and the metabolic burden induced by such complex cell engineering endeavors. This review discusses the challenges in the design of genetic control systems for cellular therapies and their translational applications.